Establishing a screening procedure for finding amino acids important for protein-protein interaction : a thesis presented in fulfilment of the requirements for the degree of Master of Science in Genetics at Massey University, Albany, New Zealand - Ghuge, Aditi Ashok (Massey University, 2020)
According to recent findings, the Gcn2 kinase is a global regulator of biological processes in the cell. In 𝘚𝘢𝘤𝘤𝘩𝘢𝘳𝘰𝘮𝘺𝘤𝘦𝘴 𝘤𝘦𝘳𝘦𝘷𝘪𝘴𝘪𝘢𝘦 (yeast), it has been shown that Gcn2 is activated by its interaction with Gcn1 in the presence of uncharged tRNAs, inducing the starvation response. The binding of Gcn2 to the RWDBD domain of Gcn1 is necessary to activate Gcn2 on medium supplemented with 3AT (3-Amino-1,2,4-Triazole) - which induces starvation for histidine. In addition, an R2295A mutation in the RWDBD domain prevents the activation of Gcn2 by disrupting the Gcn1-Gcn2 interaction. We predict that the Gcn1-Gcn2 interaction is also mediated by several other amino acids in the Gcn2 binding region of Gcn1. Therefore, to be able to test this hypothesis, a screening method was established in this research that will allow the determination of all possible amino acids in Gcn1 required for Gcn2 binding. In this thesis we aimed to establish and optimize each module of the screening procedure. One of the modules is competitive growth. This approach will take advantage of the fact that overexpressed RWDBDs in yeast can bind to Gcn2. As a result, the RWDBD disrupts Gcn1-Gcn2 interaction, and prevents Gcn2 activation, thereby preventing yeast from overcoming starvation induced by 3AT. Therefore, yeast will not be able to grow. In contrast to that, yeast strains expressing a mutated RWDBD domain incapable of disrupting the Gcn1-Gcn2 interaction will allow yeast cells to grow on starvation medium. We found that, a competitive growth assay on medium with 0.5 mM 3AT, with a duration of 120 hours, will allow for the enrichment of yeast strains expressing mutated RWDBD domains which have lost the ability to bind to Gcn2. 𝘛𝘙𝘗1 was fused in frame to the C-terminal end of the RWDBD domain which will help to eliminate truncated RWDBD domains from the library of mutated RWDBD domains. The idea was that the presence of a nonsense mutation in the RWDBD domain will lead to the premature termination of translation. As a result, 𝘛𝘙𝘗1 is not translated, and the strain remains auxotrophic for the amino acid tryptophan, whereas RWDBD domains without a nonsense mutation allow the 𝘛𝘙𝘗1 translation, conferring prototrophy for the amino acid tryptophan. For easy insertion of mutations, the Gcn2 binding region within the RWDBD was flanked with unique new restriction sites, recognized by 𝘈𝘷𝘳𝘐𝘐 and 𝘗𝘮𝘦𝘐. With the help of these new restriction sites, it is now possible to replace the Gcn2 binding region with randomly mutagenized versions. To retrieve the sequences of mutated RWDBD domains easily and efficiently, a cell culture PCR procedure was optimized. In conclusion, in this thesis the major parameters of the screening procedure were optimised.
Keywords: 310109 Proteomics and intermolecular interactions (excl. medical proteomics)